Methodological aspects of serosurveillance in resource‐poor settings. Issue 1 (9th April 2018) - Sternberg Lewerin, Susanna; Wolff, Cecilia; Masembe, Charles; Ståhl, Karl; Boqvist, Sofia; Franko, Mikael Andersson
Abstract : Animal production is important for the agricultural economy in low‐income countries, but is threatened by infectious diseases. Serosurveys are conducted for different reasons such as disease detection, risk factor studies, disease monitoring and establishing disease‐free status. Most reports on such serosurveys include some discussion about methodological constraints but still, by necessity, rely on serological results for case definition. This study uses a cross‐sectional serosurvey for foot‐and‐mouth disease (FMD), Rift Valley fever (RVF) and contagious bovine pleuropneumonia (CBPP) in cattle in three districts in Western Uganda to illustrate the limitations of this approach, addressing the questions of what flaws can be expected in sampling and diagnostics and how these influence the results. The target was to collect blood samples from 60 cattle herds per district. To reflect the recent infection history of the herd, young animals (two to five years) were prioritised. The farmers were interviewed about management, cattle trade, cattle health and vaccination. Commercial ELISAs were used for serological analyses: for CBPP the IDEXX CBPP Mycoplasma mycoides subspecies mycoides antibody test kit, for RVF the ID Screen Rift Valley Fever competitive ELISA, and for FMD the PrioCHECK FMDV NS. Apparent prevalence, true prevalence and associations with herd characteristics were assessed. The sampling plans could not be entirely fulfilled, nor the number of tests run in the laboratory. There were reactors to all three diseases with an apparent prevalence of approximately 30 per cent for CBPP, 6 per cent for RVF and 7 per cent for FMD. Calculation of true prevalence based on test sensitivity and specificity resulted in a slightly higher prevalence figure for CBPP and lower figures for RVF and FMD. The study illustrates the importance of considering diagnostic test performance when interpreting results from serosurveys, and the challenge of representative sampling and laboratory work in low‐income countries.